Synergistic effect of alkaline and heat treatment in inhibiting syneresis of CaSO₄-induced cold-set peanut protein isolate gel: Insights into structural modifications and gelation kinetics - Jing Chen; Rui Li; Zining Fan; Yu Wang; Yuntao Wang; Yanhong Bai (Food Chemistry, 2026)

Geothermal exploration of the Yala River segment of the Xianshuihe Fault Zone, eastern Tibetan Plateau: Insights from CSAMT surveys and deep drilling - Xinwei WANG; Zining MA; Nanan GAO; Tinghao WANG; Fan YANG; Shaochuan SUN; Pengfei XIANG (Geothermics, 2026)

Effect of combined treatment of pH-shifting and mild heating on gel properties of transglutaminase induced cold-set peanut protein isolate gel - Jing Chen; Si Qiu; Rui Li; Zining Fan; Yu Wang; Yuntao Wang (Food Research International, 2025)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Beneficial action of cinnamic acid against ovarian cancer via network pharmacology analysis and the pharmacological activity assessment - Rong Fan; Zining Liang; Qing Wang; Sizhe Chen; Shiting Huang; Jiansu Liu; Rui Huang; Jie Chen; Feilan Zhao; Wei Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of supplementation of cryopreservation media with cysteine on the post-thaw quality and fertility of brown-marbled grouper (Epinephelus fuscoguttatus) spermatozoa - Sen Yang; Bin Fan; Xinghan Chen; Zining Meng (Theriogenology, 2023)

Corrigendum: The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang Yang; Tong Wang; Sen Yang; Xi Wu; Wenhua Huang; Bin Fan; Junhong Xia; Zining Meng; Xiaochun Liu (Frontiers in Marine Science, 2021)

The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang Yang; Tong Wang; Sen Yang; Xi Wu; Wenhua Huang; Bin Fan; Junhong Xia; Zining Meng; Xiaochun Liu (Frontiers in Marine Science, 2021)
Asynchrony of sexual maturity is a huge limitation in the reproduction of grouper sperm. Cold storage of sperm is an effective method to solve the problem of asynchronization. However, sperms gradually lose their activity with the prolonged storage time in vitro . In order to explore causes, the effects of cold storage on transcriptome, proteome and oxidation resistance of giant grouper sperm were analyzed. Firstly, the absolute RNA quantity and consistent transcripts existed in each spermatozoon were estimated. With the prolonged storage, the RNA quantity gradually decreased both in the cytoplasm and in the mitochondria of the spermatozoon. The decreased transcripts were mainly enriched with energy metabolism and stress response. Similar to RNAs, the absolute protein quantity was also significantly decreased during the storage of sperm. Decreased proteins were mainly enriched with the oxidative phosphorylation pathway. Proteins involved in the oxidative phosphorylation showed a faster degradation rate compared to the average total protein. In addition, the oxidation resistance and adenosine triphosphate (ATP) contents showed a significant decrease in the sperm during storage in vitro . These results implied that damages of transcriptome, proteome, and oxidation resistance have negative effects on the normal functions of sperm, especially their energy metabolism. The present study provides essential foundation for improving the storage of sperm in vitro .

Cryopreservation of sperm in brown-marbled grouper (Epinephelus fuscoguttatus) - Sen Yang; Bin Fan; Xinghan Chen; Zining Meng (Aquaculture International, 2020)